Technical Losses across Distribution Networks in Nigeria and Mitigative Measures: A Review - Gerard Nonso Obiora; Godwin Osariemen Igbinosa; Collins Belouebi Fiemobebefa (ABUAD Journal of Engineering Research and Development)
The different distribution companies (DisCOs) in Nigeria constantly battle with the issue of technical losses on their respective distribution networks. And this is one factor that heavily affects their revenue. Though, technical losses are inevitable because they cannot be totally eliminated but can be rather reduced. This paper identifies lengthy distribution lines, worn-out equipment, insufficient size of conductors of distribution lines, no growth provision of system, unequal load distribution of the three phases of low tension lines, low voltage, overloading of distribution lines, load factor effect, low power factor, abnormal operating conditions, transformer sizing and selection, location of distribution transformers, feeder length, poor workmanship, use of overrated distribution transformers, efficiency of equipment and lack of proper maintenance as some of the root causes of technical losses.  In addition, practicable solutions are provided on ways the identified technical losses can be curbed on the networks of the distribution companies if implemented. The focus of this survey is to present the prevalent factors that induce technical losses on the DisCOs networks and the measures that can be taken to limit the occurrence of this class of losses. This assessment will aid industry experts, potential investors and other investigators in taking appropriate decisions on projects within this field.